Toward Transparent Village Tourism Governance: Insights from Banyumili’s Principal-Agent Dilemma - Aminullah Aminullah (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study explores governance dynamics within Banyumili Tourism Village in Pasuruan Regency, Indonesia, through the lens ofprincipal-agent theory. Using a qualitative case study design, data were collected from 31 stakeholders including 22 Pokdarwis managers, 3 local government officials, 3 private sector actors, and 3 academics through in-depth interviews, field observations, and a Focus Group Discussion (FGD). Thematic analysis using Atlas.ti revealed five central themes: unequal partnership structures, information asymmetry, moral hazard, adverse selection, and weak collaborative mechanisms. The findings highlight howPokdarwis’ dominant position in information control led to deviations from agreed tourism plans, exclusion of key stakeholders, and challenges in ensuring transparency and accountability. The study contributes to tourism governance literature by emphasizing the need for contract clarity, participatory oversight, and stronger checks to align community-based tourism with inclusive and sustainable development goals. Future research should examine comparative models of tourism partnership governance insimilar rural contexts.